Assessment of the possibility of surgical masks re-use after a sterilization process in the pandemic condition of COVID-19. Issue 17 (September 2022) - Zimniewska, Malgorzata; Witmanowski, Henryk; Kicinska-Jakubowska, Anna; Jundzill, Arkadiusz; Kwiatkowska, Edyta; Romanowska, Barbara; Malinowski, Lukasz B
The aim of this study was to explore the possibility to re-use disposable masks in order to prevent excessive waste generation during the pandemic period. The COVID-19 pandemic has caused rapidly increasing waste production resulting from the necessity of common usage of disposable personal protective equipment. This research covers the evaluation of the structure of surgical masks subjected to a threefold steam, gas or plasma sterilization process in order to verify the possibility of their re-use. The results of the study showed that gas sterilization even after three cycles did not cause significant changes in mask structure or air permeability. Hydrogen peroxide plasma sterilization caused significant changes in the structure of layer A after the third cycle of sterilization; nonetheless, it did not influence the air permeability of the mask. A significant reduction in the cover ratio of layers composing surgical masks causes an increase of air permeability in the case of steam sterilization, leading to a reduction of the mechanical ability to prevent the penetration of microorganisms. The reduction in cover ratio limits the filtration efficiency. Surgical masks subjected to threefold gas sterilization can be recommended for re-use. This allows one to use the mask thrice, ensuring safety for users and limiting the mask-waste production to one-third of the volume compared with when the mask is used once. The volume of mask-waste can be reduced with the application of the sterilization process for used masks during the pandemic period. Currently, it is not possible to sterilize all one-use masks, but implementation of this method in hospitals and medical centers is a step in the pro-environmental direction.